Triazoloquinoxalines-based DNA intercalators-Topo II inhibitors: design, synthesis, docking, ADMET and anti-proliferative evaluations - Alaa Elwan; Helmy Sakr; Abdel-Ghany A. El-Helby; Ahmed El-morsy; Mohamed A. Abdelgawad; Mohammed M. Ghoneim; Mohamed El-Sherbiny; Khaled El-Adl (Journal of Enzyme Inhibition and Medicinal Chemistry)
Sixteen [1, 2, 4]triazolo[4,3-a]quinoxalines as DNA intercalators-Topo II inhibitors have been prepared and their anticancer actions evaluated towards three cancer cell lines. The new compounds affected on high percentage of MCF-7. Derivatives 7e, 7c and 7b exhibited the highest anticancer activities. Their activities were higher than that of doxorubicin. Molecular docking studies showed that the HBA present in the chromophore, the substituted distal phenyl moiety and the extended linkers enable our derivatives to act as DNA binders. Also, the pyrazoline moiety formed six H-bonds and improved affinities with DNA active site. Finally, 7e, 7c and 7b exhibited the highest DNA affinities and act as traditional intercalators of DNA. The most active derivatives 7e, 7c, 7b, 7g and 6e were subjected to evaluate their Topo II inhibition and DNA binding actions. Derivative 7e exhibited the highest binding affinity. It intercalates DNA at IC50 = 29.06 µM. Moreover, compound 7e potently intercalates DNA at an IC50 value of 31.24 µM. Finally, compound 7e demonstrated the most potent Topo II inhibitor at a value of 0.890 µM. Compound 7c exhibited an equipotent IC50 value (0.940 µM) to that of doxorubicin. Furthermore, derivatives 7b, 7c, 7e and 7g displayed a high ADMET profile.